Pengaruh Fungsi Manajemen Koperasi Pondok Pesantren dan Etos Kerja Islami Terhadap Pembentukan Jiwa Wirausaha Santri di Pondok Pesantren Al-Qodiri Jember: (The Influence of the Management Function of the Islamic Boarding School Cooperative and Islamic Work Ethicson the Formationof the Santri Entrepreneurial Spiritat the Al-Qodiri Islamic Boarding School, Jember) - Zainuri Zainuri; Agus Mahardiyanto; Ravida Mawadatur Rohmah (UPT Penerbitan Universitas Jember, 2021)
This research was conducted to determine the effect of the cooperative management function which consists of planning, organizing, actuating, controlling, and Islamic work ethic on the formation of the entrepreneurial spirit of the santri at the Al-Qodiri Islamic Boarding school, Jember. This research is classified as confirmatory research with SEM analysis techniques. The population in this study were all members of the Al-Qodiri Jember Islamic boarding school cooperative(Kopontren), in total of 1,300 people. Sampling using probability technique and the quota sampling technique, so that 150 respondents were selected as the research sample. Data in this research is collected using questionnaire and direct interviews with the board and Kopontren members. Furthermore, the analysis is carried out using SEM analysis. The results show that planning, organizing, actuating, controlling, and Islamic work ethics have a significant direct effect on the formation of the entrepreneurial spirit of the santri. This implies that it is important to actualize management functions in every Kopontren activity and operation so that the entrepreneurial spirit of the santri is better honed. Planning, organizing, actuating, controlling have an indirect significant effect on the for mation of the entrepreneurial spirit of the santri through Islamic work ethic as an intervening variable. This shows the importance of fostering the Islamic work ethic of the Al Qodiri Kopontren students as an effort to form the entrepreneurial spirit of the santri even though the impact is indirect.